2011
DOI: 10.1002/cncr.26031
|View full text |Cite
|
Sign up to set email alerts
|

Solitary plasmacytomas

Abstract: BACKGROUND:The objective of this study was to review the outcome of patients with solitary plasmacytoma (SP) after definitive radiation therapy. METHODS: The authors retrospectively reviewed 84 patients with SP who were diagnosed and treated at The University of Texas MD Anderson Cancer Center during 1988 to 2008. The impact of tumor anatomic site, tumor size, and the presence of serum and urinary paraprotein at diagnosis was assessed on local control, survival, and the risk of developing multiple myeloma (MM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 31 publications
4
41
1
Order By: Relevance
“…Malignant plasma cells may interact with the marrow stroma and an extensive cytokine network resulting in osteolytic destruction of bone, or in some cases, producing extramedullary expansion or soft tissue plasmacytomas. In the absence of additional lesions, and other features of a systemic plasma cell disorder, fewer than 5% of patients with a plasma cell dyscrasia will be diagnosed with a solitary bone or extramedullary plasmacytoma [4,5] It is important to distinguish these patients from counterparts with myeloma since approximately 35–65% of these patients may be curable with definitive radiotherapy [5]…”
Section: Introductionmentioning
confidence: 99%
“…Malignant plasma cells may interact with the marrow stroma and an extensive cytokine network resulting in osteolytic destruction of bone, or in some cases, producing extramedullary expansion or soft tissue plasmacytomas. In the absence of additional lesions, and other features of a systemic plasma cell disorder, fewer than 5% of patients with a plasma cell dyscrasia will be diagnosed with a solitary bone or extramedullary plasmacytoma [4,5] It is important to distinguish these patients from counterparts with myeloma since approximately 35–65% of these patients may be curable with definitive radiotherapy [5]…”
Section: Introductionmentioning
confidence: 99%
“…Balducci et al (2011) described re-calcification in patients with osteolytic lesions due to diverse plasma cell neoplasm in 50% and identified as complete remission in 38%. Mose et al (2000) also found a relevant effect in concurrent chemotherapy, but no difference in re-calcification in terms of radiation dose probably due to the low variability in total doses (30)(31)(32)(33)(34)(35)(36). In summary, available data indicate that higher radiation doses result in improved re-calcification.…”
Section: Results:-mentioning
confidence: 96%
“…However, previous studies indicated that a combination treatment may provide the best results (7). The majority of EMPs involve the head and neck regions (8), although different anatomical sites, including the gastrointestinal tract, central nervous system, thyroid gland and breast may also be affected (7). However, it is rare that EMPs present initially with simultaneous intracranial and renal infiltration.…”
Section: Introductionmentioning
confidence: 99%